1993
DOI: 10.1161/01.res.72.6.1245
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II is mitogenic in neonatal rat cardiac fibroblasts.

Abstract: muscle, effects on cardiac metabolism, and vasoconstriction of blood vessels.' In addition, clinical studies demonstrating the efficiency of angiotensin converting enzyme (ACE) inhibitors in the treatment of heart failure,2 myocardial ischemia,3 4and hypertension5.6 suggest that Ang II directly promotes pathological cell growth that participates in remodeling of the failing heart. Several animal studies have implicated Ang II in cardiac hypertrophy associated with hypertension; for instance, in a rat model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
160
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(174 citation statements)
references
References 35 publications
5
160
0
3
Order By: Relevance
“…31 In neonatal rat cardiac fibroblast, angiotensin II stimulated the synthesis of protein, DNA and RNA, which was inhibited by EXP-3174, suggesting that angiotensin II-induced cardiac hypertrophy is, in part, secondary to stimulated increases in nonmyocyte cellular growth. 32 In cultured adult rat cardiac fibroblasts, angiotensin II stimulated the mRNA expression of collagen type I and III, the major fibrillar collagens in the heart, and decreased the mRNA of collagenase, the key enzyme for interstitial collagenase degradation. Losartan abolished the gene expression of collagen and had no effect on collagenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…31 In neonatal rat cardiac fibroblast, angiotensin II stimulated the synthesis of protein, DNA and RNA, which was inhibited by EXP-3174, suggesting that angiotensin II-induced cardiac hypertrophy is, in part, secondary to stimulated increases in nonmyocyte cellular growth. 32 In cultured adult rat cardiac fibroblasts, angiotensin II stimulated the mRNA expression of collagen type I and III, the major fibrillar collagens in the heart, and decreased the mRNA of collagenase, the key enzyme for interstitial collagenase degradation. Losartan abolished the gene expression of collagen and had no effect on collagenase activity.…”
Section: Discussionmentioning
confidence: 99%
“…In j3h-UTR expressing cells, Ang II stimulated an intracellular calcium transient with a sustained phase, which mimics Ang II stimulated calcium transients in cells isolated from tissues expressing endogenous AT " receptors (e.g. vascular smooth muscle cells, adrenal zona glomerulosa cells and cardiac fibroblasts) [16,30,31]. In contrast, Ang II stimulation of k3h-UTR cells resulted in a more transient calcium response which returned to basal levels within 50 s. Together, these observations suggest that the 3h-UTR of the AT "A receptor has a role in cell signalling and growth, and that the cell is able to distinguish between the j3h-UTR and k3h-UTR transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…31 We have recently shown that unlike in cardiac myocytes, Ang II-induced MAP kinase activation is suppressed by tyrosine kinase inhibitors but is not affected by PKC downregulation in cardiac fibroblasts. 32 Ang II-induced MAP kinase activation was abolished by pretreatment with pertussis toxin and by overexpression of the G␤␥ subunit-binding domain of the ␤-adrenergic receptor kinase 1 in cardiac fibroblasts.…”
Section: Ang Ii-induced Signal Transduction Pathwaysmentioning
confidence: 97%